The Steel-Blue Peppering and Systemic Eosinophilia: Dermoscopic-Histopathological Correspondence of the Tyndall Effect in Generalized Fixed Drug Eruption - William Yudistha Anggawirya; Shienty Gaspersz; Ferra Olivia Mawu; Thigita Aga Pandaleke; Anggi Anastasia Ursula Dien (HM Publisher, 2026)
Background: Generalized fixed drug eruption (GFDE) represents a severe and distinctive variant of delayed-type hypersensitivity, characterized by widespread, recurrent pigmentary lesions involving at least three anatomical sites. Its clinical presentation often mimics extensive lichenoid dermatoses or infectious conditions such as Hansen’s disease, leading to significant diagnostic delays, particularly in geriatric populations with polypharmacy. While dermoscopy offers a non-invasive bridge to histopathology, specific correlative studies in generalized cases remain scarce. Case presentation: We report the case of a 69-year-old male presenting with diffuse, well-demarcated, violaceous plaques affecting the face, trunk, extremities, and genitalia. The eruption demonstrated a pathognomonic acute latency, recurring at identical anatomical sites within six hours of re-exposure to an unprescribed analgesic cocktail. High-definition non-contact polarized dermoscopy identified two distinct morphological patterns: a brown starburst pattern with central clearing on the extremities and diffuse steel-blue peppering on femoral lesions. Notably, the patient exhibited a mixed immunophenotype characterized by marked eosinophilia (2,080 cells per microliter) and elevated total immunoglobulin E (2,295 IU per milliliter). Parasitic infection was rigorously excluded via negative stool examination and serology, and a Naranjo probability score of 10 confirmed a definite adverse drug reaction. Histopathological examination confirmed interface dermatitis with necrotic keratinocytes and marked pigment incontinence. Conclusion: This study illustrates that steel-blue peppering is a reliable dermoscopic surrogate for deep dermal pigment incontinence via the Tyndall effect. The discrepancy between high systemic eosinophilia and low tissue eosinophilia suggests a complex, potentially mixed-hypersensitivity phenotype in generalized cases, distinct from classic localized fixed drug eruption.